Public Awareness and Perception of TEVET Activities in Malawi - Manda, Levi Zeleza (Journal of Technical Education and Training, 2017)
This study assessed the impact of Information, Education, Communication and Marketing (IECM) strategy by Malawi’s Technical, Entrepreneurial and Vocational Education and Training Authority (TEVETA) on potential clients’ awareness of the organisation’s existence understanding of policies on and HIV/AIDS and Gender, and their perception of the importance of TEVET activities in Malawi. A structured questionnaire was deployed to gather data from a sample of 585 interviewees recruited using a two step sampling design. The findings suggest that the IECM activities were not successful in creating awareness of TEVETA Malawi’s presence and TEVET amongst urban, peri-urban and rural Malawians. Further, the study found that potential client knowledge of what TEVETA does and its policies relating to gender and HIV/AIDS inclusiveness was limited. For TEVET to become popular and help in driving national economic growth, the study recommends that TEVETA Malawi should espouse a targeted integrated public communication strategy comprising use of multiple communication channels, strategic placement IECM materials and use of multiple languages.